Nucleotide proofreading functions by nematode RAD51 paralogs facilitate optimal RAD51 filament function - Špírek, Mário; Taylor, Martin R G; Belan, Ondrej; Boulton, Simon J; Krejci, Lumir (Nature communications, 2021)
The RAD51 recombinase assembles as helical nucleoprotein filaments on single-stranded DNA (ssDNA) and mediates invasion and strand exchange with homologous duplex DNA (dsDNA) during homologous recombination (HR), as well as protection and restart of stalled replication forks. Strand invasion by RAD51-ssDNA complexes depends on ATP binding. However, RAD51 can bind ssDNA in non-productive ADP-bound or nucleotide-free states, and ATP-RAD51-ssDNA complexes hydrolyse ATP over time. Here, we define unappreciated mechanisms by which the RAD51 paralog complex RFS-1/RIP-1 limits the accumulation of RAD-51-ssDNA complexes with unfavorable nucleotide content. We find RAD51 paralogs promote the turnover of ADP-bound RAD-51 from ssDNA, in striking contrast to their ability to stabilize productive ATP-bound RAD-51 nucleoprotein filaments. In addition, RFS-1/RIP-1 inhibits binding of nucleotide-free RAD-51 to ssDNA. We propose that 'nucleotide proofreading' activities of RAD51 paralogs co-operate to ensure the enrichment of active, ATP-bound RAD-51 filaments on ssDNA to promote HR.
Keywords: Rad51 Recombinase; interferometrie; adenosintrifosfát; Adenosine Diphosphate; sekvenční homologie aminokyselin; druhová specificita; Sequence Homology, Amino Acid; Protein Binding; adenosindifosfát; rekombinasa Rad51; DNA, Single-Stranded; zvířata; nukleotidy; Caenorhabditis elegans; Caenorhabditis elegans Proteins; stabilita proteinů; Fluorescence; Nucleotides; jednovláknová DNA; proteiny Caenorhabditis elegans; Adenosine Triphosphate; Interferometry; vazba proteinů; Species Specificity; fluorescence; Animals; Protein Stability